An Epidemiological and Clinical Study on Scorpionism in Hospitalized Children in Khuzestan, Iran - B Vazirianzadeh; F Farhadpour; M Hosseinzadeh; M Zarean; SA Moravvej (Tehran University of Medical Sciences, 2012)
Background: Scorpion sting is a public health problem in Khuzestan, South-West Iran. The aims of the current study were to monitor the hospitalized children, due to scorpion sting, and releasing more clinical and epidemiologic data related to scorpionism in this Province. Methods: In this retrospective study, the data of scorpion sting victims, among the hospitalized children in Abuzar Children Hospital of Ahvaz Jundi Shapur University of Medical Sciences, was analyzed from the points of epidemiological and clinical aspects in 2006. Results: The scorpion species of 18 files out of 57 were recognized accurately, using Farzanpay key of Iranian scorpions, as Androctonus crassicauda (Scorpionida: Buthidae) and Hemiscorpious lepturus (Scorpionida: Hemiscorpiidae). Conclusion: The most scorpionism emergencies among the children in the Khuzestan should be paid to those species. However, H. lepturus sting emergencies are in the top of attention among the children.